Plasma-wall interaction of advanced materials. (August 2017) - Coenen, J.W.; Berger, M.; Demkowicz, M.J.; Matveev, D.; Manhard, A.; Neu, R.; Riesch, J.; Unterberg, B.; Wirtz, M.; Linsmeier, Ch.
Abstract: DEMO is the name for the first stage prototype fusion reactor considered to be the next step after ITER. For the realization of fusion energy especially materials questions pose a significant challenge already today. Advanced materials solution are under discussion in order to allow operation under reactor conditions [1] and are already under development used in the next step devices. Apart from issues related to material properties such as strength, ductility, resistance against melting and cracking one of the major issues to be tackled is the interaction with the fusion plasma. Advanced tungsten (W) materials as discussed below do not necessarily add additional lifetime issues, they will, however, add concerns related to erosion or surface morphology changes due to preferential sputtering. Retention of fuel and exhaust species are one of the main concerns. Retention of hydrogen will be one of the major issues to be solved in advanced materials as especially composites and alloys will introduce new hydrogen interactions mechanisms. Initial calculations show these mechanisms. Especially for Helium as the main impurity species material issues arise related to surfaces modification and embrittlement. Solutions are proposed to mitigate effects on material properties and introduce new release mechanisms.